1998
DOI: 10.1109/20.706534
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of large Barkhausen jump on length of a vicalloy fine wire with torsion stress

Abstract: This paper concerns with the magnetic sensor using a vicalloy wire with uniaxial anisotropy and torsion stress. In the magnetic sensor using a compound magnetic wire, the relationship among the wire length, magnetization state and the output voltage based on the large Barkhausen jump was investigated. When the specimen wire was short, magnetizations of soft and hard layers was stable only when they are in anti-parallel due to demagnetizing field. This result indicated that the large output voltage might be obt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Due to the magnetic anisotropy, the wire is preferably magnetized in one of the two directions along the wire axis (Abe et al, 1997). No matter how slow the external magnetic field changes, the transition between these two bi-stable states, often referred to as the macroscopic Barkhausen effect, takes place almost instantaneously (Abe et al, 1998;Huening and Backes, 2020). It is associated with a release of magnetic energy that can be picked up as induction voltage in a surrounding coil.…”
Section: Wiegand Effectmentioning
confidence: 99%
“…Due to the magnetic anisotropy, the wire is preferably magnetized in one of the two directions along the wire axis (Abe et al, 1997). No matter how slow the external magnetic field changes, the transition between these two bi-stable states, often referred to as the macroscopic Barkhausen effect, takes place almost instantaneously (Abe et al, 1998;Huening and Backes, 2020). It is associated with a release of magnetic energy that can be picked up as induction voltage in a surrounding coil.…”
Section: Wiegand Effectmentioning
confidence: 99%
“…The Wiegand effect was initially observed in NiFe alloy wire by John R. Wiegand in 1974 [1,2]. It was reported that the wire made of FeCoV alloy offered optimum performance in generating the Wiegand effect [3][4][5][6][7][8][9]. The diameter of the Wiegand wire used in the prior research was about 0.25 mm.…”
Section: Wiegand Effectmentioning
confidence: 99%
“…A bistable magnetic structure is formed in FeCoV wires by twisting and annealing treatments. The magnetic properties of FeCoV wires have been reported in terms of annealing and torsion stress [19,20]. After the wires are twisted, their outer layers near the surface become magnetically soft with a low coercivity, whereas the center core remains magnetically hard with a high coercivity [20].…”
Section: Introductionmentioning
confidence: 99%